Wheat crop in Rio Grande do Sul state, Brazil, 2019. - CASTRO, R. L. de (2021)
Rio Grande do Sul is one of the main wheat-producing states in Brazil. This study analyzed the wheat crop in Rio Grande do Sul in 2019.